2017
DOI: 10.5455/jice.20170606094119
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological values of cassava and its potential for diabetes and dyslipidaemia management: knowledge survey and critical review of report

Abstract: Background:Beyond nutritional values are the pharmacological potentials of cassava comparative with other staple carbohydrate plant-based foods such as wheat. The knowledge of applicability to diabetes and its cardiovascular complications management seems not just limited but unacknowledged. As a preliminary study, a community’s knowledge of pharmacological value of cassava is investigated.Methods:Descriptive observational study using questionnaire-based “cross-sectional” survey was conducted. 136 Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Most studies used a correlational/comparative design. Specifically, 37 followed a cross-sectional design [ 2 , 7 , 10 , 30 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] ( Table 1 ) and two followed experimental designs [ 43 , 94 ] ( Table 2 ). Three studies used qualitative methodology [ 95 , 96 , 97 ] and two used mixed-method (qualitative and quantitative) research designs [ 98 , 99 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used a correlational/comparative design. Specifically, 37 followed a cross-sectional design [ 2 , 7 , 10 , 30 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] ( Table 1 ) and two followed experimental designs [ 43 , 94 ] ( Table 2 ). Three studies used qualitative methodology [ 95 , 96 , 97 ] and two used mixed-method (qualitative and quantitative) research designs [ 98 , 99 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…49 Cassava is believed to be useful in treating snake or scorpion bites due to its bioactive chemical contents in different cultures, such as India and Papua New Guinea. 78 It is also consumed as a wheat alternative in Western cuisine for patients diagnosed with celiac disease. 79…”
Section: Resultsmentioning
confidence: 99%
“…49 Cassava is believed to be useful in treating snake or scorpion bites due to its bioactive chemical contents in different cultures, such as India and Papua New Guinea. 78 It is also consumed as a wheat alternative in Western cuisine for patients diagnosed with celiac disease. 79 Various methods of cassava utilization for food are adopted in South America and West Africa, including grating and pounding cassava tubers into a pulp, shaping them into pies or cakes, cooking in various ways, and making soups and drinks.…”
Section: Traditional Applications Of Cassava In Ethnomedicine and Cul...mentioning
confidence: 99%
“…In a previously published critical analysis, it was reported that carbohydrate or fibre and fat or fibre ratios are negligible in the raw products, but highest in wheat flour and higher in yam relative to cassava flour. 41 That is, evidence has been presented that, all things being equal, cassava flour may contribute the least fat and most fibres while yam flour follows. It was concluded that since fat is pro-obesity and pro-diabetic, while fibre is antidyslipidaemic; wheat may possess the least pharmacological values relative to the indigenous carbohydrate food crops of Delta State Nigeria.…”
Section: Comparison Of Wheat With Cassava and Yammentioning
confidence: 99%